Ingasaponin, a complex triterpenoid saponin with immunological adjuvant activity from Inga laurina. (February 2016) - Cruz, Maria de Fátima Simão Jucá; Pereira, Gabriela Moysés; Ribeiro, Marcela Gonçalves; da Silva, Ari Miranda; Tinoco, Luzineide Wanderley; da Silva, Bernadete Pereira; Parente, José Paz
Highlights: A new complex triterpenoid saponin was isolated from Inga laurina . The chemical structure was established by spectroscopic techniques and chemical conversions. The compound exhibited significant immunological adjuvant activity. Graphical abstract: Abstract: As part of our search of bioactive saponins from Brazilian plants, phytochemical study of the seeds of Inga laurina led to the isolation of a new complex triterpenoid saponin, named ingasaponin. It is the first saponin isolated from a species of Inga genus. It was isolated by using chromatographic methods and its structural elucidation was performed using detailed analyses of 1 H and 13 C NMR spectra including 2D-NMR spectroscopic techniques and chemical conversions. Its structure was established as 21-[[(2 E, 6 S )-6-[[6-deoxy-4-O-[(2 E, 6 S )-6-[( β -d -glucopyranosyl)oxy]-2, 6-dimethyl-1-oxo-2, 7-octadienyl]-[( β -d -glucopyranosyl)oxy]-2, 6-dimethyl-1-oxo-2, 7-octadienyl]-[( β -d -glucopyranosyl)oxy]-2, 6-dimethyl-1-oxo-2, 7-octadienyl]-[( β -d -glucopyranosyl)oxy]-2-(hydroxymethyl)-6-methyl-1-oxo-2, 7-octadienyl]oxy]-16-hydroxy-3-[[ O - β -d -xylopyranosyl-(1→2)-O- α -l -arabinopyranosyl-(1→6)-2-(acetylamino)-2-deoxy- β -d -glucopyranosyl]oxy]-(3 β, 16 α, 21 β )-olean-12-en-28-oic acid O- α -l -arabinofuranosyl-(1→4)-O-[ β -d -glucopyranosyl-(1→3)]-O-6-deoxy- α -l -mannopyranosyl-(1→2)- β -d -glucopyranosyl ester (1 ). The hemolytic potential of1 was evaluated using in vitro assays, and its adjuvant activity on the cellular immune response against ovalbumin antigen was investigated using in vivo models.